DESIGN PRINCIPLES OF 'FOOD SENSITIVE URBAN DESIGN' IN COASTAL AREA INDONESIA (STUDY CASE : KENJERAN COASTAL, SURABAYA) - Sukma Ningrati, Annisa
Food security and stability of food access are critical issues in urban development, particularly in developing countries like Indonesia, which face food instability and rapid population growth. Various concepts of food security, such as Food Resilient, Food Security, and Food Sensitive Planning and Urban Design (FSPUD), have been implemented in developed countries and offer innovative solutions for urban planning that support sustainable food systems. FSPUD, initially developed in Australia, integrates food security principles into urban design, focusing on food resource management, access, and social interactions to strengthen food security and mitigate the impacts of climate change. However, a key challenge in Indonesia is the dualism of urban structure, where urban areas are divided into formal and informal zones, affecting infrastructure and food access. Climate change, including rising sea levels threatening coastal areas, exacerbates this issue, necessitating adjustments to FSPUD standards, particularly in informal settlements or urban villages located in coastal regions, to enhance sustainable food security.